Marine Structures - Oterkus, Erkan (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Structural mechanics is an important field of engineering. The main goal of structural mechanics is to ensure that structures are safe and durable so that catastrophic situations can be prevented, which can otherwise cause loss of life, environmental pollution and financial losses. Depending on the uses of the structure and the conditions that the structure is subjected to, special treatment may be required for the analysis. Specifically, marine structures are subjected to harsh environmental conditions due to the marine environment, which can cause several different damage mechanisms including fatigue and corrosion. This book on "Marine structures" considers a wide range of areas related to marine structures and provides a compilation of numerical and experimental studies related to "Marine structures" research.